Evaluation of the dynamic modulus of elasticity of a pozzolanic mortar of rice husk ash reinforced with sugarcane bagasse - Datchossa, Tiambo Abbas; DOKO, KOUANDETÉ VALERY; Olodo, E.T. Emmanuel (My University, 2023)
In the last decades, many works are going in the direction of valorization of vegetable biomass. The aim of the present work is to determine the dynamic modulus of elasticity of a cementitious matrix composite with rice husk ash pozzolan reinforced with sugarcane bagasse. To do this, we formulated mortars in which we varied the volume fraction of sugarcane bagasse and kept 10% of rice husk ash as a cement replacement. The sugarcane bagasse fractions of 0%, 3%, 6% and 10% yielded the mortars denoted RHA10, R10SB3, R10SB6, R10SB10, respectively. We have experimentally determined the density, the porosity of the different mortars obtained. Then, we determined by ultrasound test the speed of propagation of sound waves in the different mortars before calculating their dynamic moduli of elasticity. The results of the study show that the porosity, density, and dynamic modulus of elasticity of RHA10 mortars decreases with the increase of the volume fraction of sugarcane bagasse. The dynamic moduli of RHA10, R10SB3, R10SB6 and R10SB10 are 3.25GPa, 3.14GPa, 2.56GPa, 1.71GPa respectively with a porosity-dynamic modulus correlation R² of 0.94.
Keywords: Matrix; Rice husk ash; Sugar cane bagasse; Porosity; Dynamic modulus of elasticity